Relative clauses in the Ll-acquisition of Turkish - Korfilt Jaklin; International Conference on Turkish Linguistics (15.) (2010) (Szeged) (2012)
This study examines the acquisition patterns of head-final relative clauses (RCs) in Turkish in monolingual1 and bilingual children. It has been claimed that both subject- and object-RCs are acquired by children earlier in Indo-European languages, compared to children acquiring Turkish RCs, because of the lack of wh-pronouns and overt complementizers, the differences between nominalized embedded clauses and finite main clauses, and the supposed complexity of nominalization and agreement morphology. It is claimed in Slobin (1986) that these properties make Turkish RCs difficult to acquire. By using experimental elicitation with monolingual Turkish children and longitudinal naturalistic acquisition data from a Turkish child in the Netherlands, we checked the validity of earlier claims regarding the acquisition of relative clauses. Our experiments as well as the longitudinal corpus show that young children (of comparable age as their counterparts acquiring Indo-European languages) do use RC-morphology and syntax correctly for the most part. While they may use RC constructions less frequently than those counterparts, their competence in this area is comparable. Our results show that Slobin (1986 and related work) and Çagn (2006) were wrong in claiming that children under 5 acquiring Turkish lack the morpho-syntax for head-final RCs without complementizers and relative pronouns in Turkish.
Keywords: Bölcsészettudományok; Nyelvek és irodalom